Remaining Musics: Lithuanian Karaimes - Firkavičiūtė, Karina (Acta Orientalia Vilnensia, 2001)
The article discusses three principal parts of the musical heritage of Lithuania’s Karaimes both in a parochial, as well as in a broader liturgical and social context. The author analyses the specificity of their locale features and compares them with analogous manifestations in other Karaime communities (emigres from Egypt and the Crimea), as well as in Judaic and Eastern Christian traditions. The comparisons confirm the authenticity of Lithuanian Karaime liturgical melodies with their original structure and the principles of sound and text harmony preserved.